Pengaruh Experiential Marketing, Electronic Service Quality, Dan Electronic Word Of Mouth Terhadap Minat Beli Ulang Pada Pengguna Lazada Di Kabupaten Badung - Ariani, Desak Putu Novi Sri; Agustina, Made Dian Putri; Diputra, Gde Indra Surya (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to determine the influence of experiential marketing, electronic service quality, and electronic word of mouth on repurchase interest in Lazada users in Badung regency. This study was conducted in Lazada, Badung Regency, the sample used was 100 respondents using the purposive sampling method. The analytical methods in this study are multiple linear regression analysis, validity and reliability tests, classical assumption tests consisting of normality tests, multicholinearity tests, heterokesdasticity tests, and hypothesis tests. Based on the results of the study, it can be seen that: (1) Experiential Marketing has a positive and significant effect on repurchase interest in Lazada users in Badung Regency. (2) Electronic Service Quality has a positive and significant effect on repurchase interest in Lazada users in Badung Regency. (3) Electronic Word of Mouth has a positive and significant effect on repurchase interest in Lazada users in Badung Regency. (4) experiential marketing, electronic service quality, and electronic word of mouth simultaneously have a positive and significant effect on repurchase interest in Lazada users in Badung Regency.